Chemical Profiling of Essential Oil Extracted from Fresh Walang Leaves (Etlingera walang (Blume) R. M. Sm.), an Indigenous Species in Banten, Indonesia - Novi, Cory; Apriliane, Keukeu Listia; Oktavia, Swastika (Universitas Muhammadiyah Surakarta, 2024)
Essential oils are a group of secondary metabolite compounds that have a distinctive aroma and are volatile. Walang leaves are one of the plants suspected of having essential oil content. This study aims to determine the constituent components of essential oil compounds from fresh walang leaves. The method used to extract essential oil from fresh walang leaves is steam distillation. The essential oil produced was analyzed using Gas Chromatography Mass Spectroscopy (GC-MS). The results showed that the essential oil of fresh walang leaves contained 15 components of essential oil compounds and 2 main components of essential oil compounds, namely: Acetic acid (CAS) Ethylic acid 24.52%, 1,2 Benzenedicarboxylic acid, bis(2-methylpropyl) ester (CAS) Isobutyl phthalate 21.09%.